Entrepreneurial Mindset: Membangun Mental Wirausaha Mandiri Sejak Bangku SMA - Anissa Sekar Kinasih; Dewi Sadiya Safitri; Syakila Sukmawati (CV. ITTC INDONESIA, 2026)
This PKM activity is expected to go beyond simply mastering entrepreneurial theory, namely being able to shape a positive mentality and attitude in responding to challenges. With an entrepreneurial mindset, students are projected to become more confident, independent, and motivated individuals to optimize their potential. This implementation uses a participatory, educational, and applied learning method. This method is designed to foster an entrepreneurial mindset in high school students and ensure active participant involvement throughout the activity process. The results of the material delivery activity through presentations indicate that students are beginning to be able to understand and identify business opportunities relevant to everyday life. Overall, this activity makes a real contribution to fostering an independent entrepreneurial mentality in high school students at Sekolah Puspita Bangsa Ciputat. The results obtained are in line with the goal of entrepreneurship education, namely to shape a young generation that is creative, independent, and ready to face future challenges.